'Are we being de‐gifted, Miss?' Primary school gifted and talented co‐ordinators' responses to the Gifted and Talented Education Policy in England. (15th October 2012) - Koshy, Valsa; Pinheiro‐Torres, Catrin
<x xml:space="preserve">Abstract</x> Over a decade ago the UK government launched its gifted and talented education policy in England, yet there has been very little published research which considers how schools and teachers are interpreting and implementing the policy. By seeking the views of the gifted and talented co‐ordinators (For ease of reference, the term gifted and talented (G&T) co‐ordinator is used throughout the paper as a generic shorthand for the research participants who were either designated school gifted and talented co‐ordinators or teachers or head teachers with responsibility for policy implementation) with responsibility for addressing the requirements of the policy, the study reported in this paper explored how primary schools in England responded to the policy. Drawing on data gathered using questionnaires with a national sample of primary schools as well as follow‐up in‐depth interviews with a sample of G&T co‐ordinators, the authors report their findings. The study found that there was considerable unease about the concept of identifying and 'labelling' a group of pupils as 'gifted and talented'. G&T co‐ordinators found it difficult to interpret the policy requirements and were responding pragmatically to what they considered to be required by the government. Curriculum provision for the selected group of gifted and talented pupils was patchy. The paper concludes by identifying a need for further professional development for teachers and by challenging the policy's over‐emphasis on identifying and labelling gifted and talented pupils. We posit whether the gifted and talented education policy would have been better introduced and enjoyed greater success by leaving the identification of pupils to one side and by placing greater emphasis on developing effective learning and teaching strategies instead.